Review paperInteractive effects of endogenous morphine, nitric oxide, and ethanol on mitochondrial processes - Kream, Richard M.; Stefano, George B. (Archives of Medical Science, 2010)
Positive evolutionary pressure has preserved the ability to synthesize chemically authentic morphine, albeit in homeopathic concentrations, throughout animal phyla. The prototype catecholamine dopamine (DA) serves as an essential chemical intermediate in morphine biosynthesis both in plants and animals, thereby providing considerable insight into the roles reciprocal “morphinergic” and catecholamine regulation of diverse physiological processes. Primordial, multi-potential cell types, before the emergence of specialized plant and animal cells/organ systems, required selective mechanisms to limit their responsiveness to environmental noise. Accordingly, cellular systems that emerged with the potential for recruitment of the free radical gas nitric oxide (NO) as a multi-faceted autocrine/paracrine signaling molecule were provided with extremely positive evolutionary advantages. Endogenous “morphinergic” in concert with NO-coupled signaling systems have evolved as autocrine/paracrine regulators of metabolic homeostasis, energy metabolism, mitochondrial respiration and energy production. Basic physiological processes involving “morphinergic”/NO-coupled regulation of cardiovascular mitochondrial function, with special emphasis on the interactive effects of ethanol, are discussed within the context of our review.